Development of E-Comic Kulturunterschiede as a Learning Media for German Culture - Marhalisa Ramadhani Ar Ridho; Miftachul Ni'mah; Desti Nur Aini; Sawitri Retnantiti (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This development research aims to develop a product in the form of digital e-comic Kulturunterschiede as a medium for learning German culture. The purpose of developing this e-comic is to provide a visualization of cultural differences between Indonesia and Germany. The digital e-comic Kulturunterschiede contains cultural learning in the form of comics that contain Indonesian culture and German culture, besides that, it also presents practice questions. The development of this e-comic is expected to train reading (lesen), and speaking (sprechen) skills. The method used in this research is research and development with a research model following the Richey, Klein and Nelson type one model. The author uses qualitative descriptive data analysis techniques with the target users being Malang State University students who have taken Landeskunde courses. Further development of this e-comic is to develop with more diverse and interactive topics, as well as further research on the effectiveness of comics as a medium for learning German.